EDITORIAL - Sayyid M. Syeed (International Institute of Islamic Thought, 1991)
Once again it is our pleasure to have the “Guiding Light” from Abdul Hm-d AbiiSulaymh under a specific title. He has arranged relevant verses from the Qur’an and the sayings of the Prophet to discuss the civilizational value of cleanliness. This approach has been appreciated by our readership. In this issue of AJISS, Ghulam-Haider Aasi sketches the relatively unknown contribution of Muslim scholars to the history of religions and their role as the true founders of this discipline. It is important for present-day Muslim historians and social scientists to realize how their predecessors conceived the reality of sociohistorical phenomenon, a view which was based upon religious ideas and practices. The history of humanity for Muslim scholars was the history of ideas and values, for they saw religion as the core and basis of all human culture and civilization and all other branches of knowledge as being directly related to and dependent upon the science of religion. In his brief paper, Aasi has brought to our attention an unexplored legacy which, if mentioned at all, is only done so casually and very briefly by the Western scholars of Islam. This unique and volumnious literature, Aasi says, still awaits its readers, analysts, critics, and translators. Khalid Blankinship, writing on the periodization of history, shows how the supposedly “world” history taught in the West has a strong Eurocentric bias, which is reflected in the currently acceptable division of history into ancient, medieval, and modem times based on what was happening in the West (i.e., Europe) at that time. He shows through his analysis of this three part periodization of history how the narrow parochial origins of the Western vision of history goes back to the idea that only Western European civilization is worthy of study. He also shows the limitations of the traditional Muslim historians, who tended to be largely isolationist in their accounts, and of the assimilating Muslim modernizers, who have accepted the subordination of their history and ideas to materialist viewpoints of the West. Blankinship argues that in light of the universality of tawhid, based on his assertion that the history of humanity is essentially a quest to know God, all human traditions contain elements that are more or less close to Islam and therefore worthy of study. He demonstrates that from an Islamic point of view, history is the universal property of everyone. As an alternative to the current Eumcentric periodhation, Blankinship postulates dividmg historical eras based on the approximate date of 600 CE, which he claims is a watershed ...